International instruments for promoting corporate social responsibility (CSR) - Tatjana Chahoud (Deutsches Institut für Entwicklungspolitik (DIE), 2005)
Corporate social responsibility (CSR) is increasingly to be found on the international agenda as globalization continues. It is by no means new, however, reaching back into the early 18th century. At that time corporate social responsibility was motivated primarily by religious or ethical convictions, although fear of radical movements also played its part. The concept of corporate social and ecological responsibility is still very vague. Typological classification is possible by reference to the actors involved. While corporate codes of conduct are restricted to the various businesses concerned, the Global Compact (GC) and the OECD Guidelines for Multinational Enterprises are the most important business-wide, global instruments. The Global Compact now focuses on ten principles, relating to the most important international agreements in the areas of human rights, labour and social standards, environmental standards and anti-corruption. While further additions have been made to the GC principles, the implementing mechanisms remain weak. The business community places the emphasis on the principle of self-regulation and the best-practice approach. The NGOs, but other actors too, criticise the absence of monitoring and of sanction mechanisms. The OECD Guidelines contrast with the GC in being the only multilaterally recognized comprehensive code to have been agreed among the governments. The principles set out in the Guidelines go much further than the GC principles, covering such aspects as taxation, consumer interests and the disclosure of information. The general principles also formulate suppliers' and subcontractors' responsibilities. The OECD Guidelines focus not on the documentation of best practices but on the discussion of issues within a tripartite structure (government, business, NGOs or employee organizations). This structure prevents individual actors from giving prominence to their activity primarily as a PR measure. The GC and OECD Guidelines must be seen not as alternatives but as complementary instruments. By strengthening regional GC networks and promoting comprehensive multi-stakeholder fora, development cooperation can do a great deal to pave the way for CSR in developing countries. To increase acceptance of the GC, more needs to be done in the monitoring sphere. As regards the OECD Guidelines, development cooperation should seek to strengthen their role in the developing countries, especially for the supply chain. Action should be taken to counteract any denial of responsibility in this sphere through the application of the Guidelines solely to investments (“investment nexus”). Increased transparency of the activities of the National Contact Points could help to increase the importance of the OECD Guidelines as a global instrument for CSR.
Keywords: 330